1 Comparison of right ventricular (RV) size and function by two dimensional echocardiography (2DTTE) and cardiac magnetic resonance imaging (CMR). (26th April 2015) - Akbar, S; Parasa, R; Alexander, J; Lee, E; Kamaruddin, H; Mathew, T
Abstract : The aim of this study was to compare the right ventricular diameter (RVD1) and tricuspid annular plane systolic excursion (TAPSE) measured by 2DTTE with volumes and EF derived from CMR. Method and results: We studied 50 patients (mean age 53 ± 17 years, 36 males and 14 females) who underwent TTE and CMR within 6 months of each other. RVD1 and TAPSE were measured by 3 independent observers (inter observer variability = 5.6% (95% CI: 4–6.8%). RV volumes were measured by 2 independent observers blinded to the TTE data (inter observer variability =5% (95% CI: 4–6.8%). For RVD1, an upper reference value of 4.2 cm was used to indicate RV dilatation and for TAPSE a lower reference value of 1.6 cm was used for systolic impairment as per current recommendations. Upper reference value for end diastolic volume (EDV) indexed to BSA, age and gender was used as the CMR cut off for RV dilatation and lower reference value for EF based on age and gender was used for systolic impairment. RVD1 showed a statistically significant correlation with RVEDV (r = 0.475, p < 0.01). The sensitivity and specificity of RVD1 >4.2 cm for predicting RV dilatation was 57% and 83% respectively. A cut off value of RVD1 >4.1 cm improved the sensitivity to 71% with no change in specificity (ROC analysis: AUC = 0.81). TAPSE did not correlate with EF (r = 0.174, p = 0.248). The sensitivity and specificity of TAPSE <1.6 cm for predicting systolic impairment was 81% and 13% respectively (ROC analysis: AUC 0.43). Adjusting the cut off of TAPSE did not improve this. Conclusions: Our data suggests that the current value of RVD1 > 4.2 cm is a poor predictor of RV dilation and lowering the value to 4.1 increases the sensitivity. TAPSE does not correlate with EF by CMR and is a poor predictor of global RV systolic impairment at any cut off value.